2013
DOI: 10.1159/000353674
|View full text |Cite
|
Sign up to set email alerts
|

Triple versus Dual Antiplatelet Therapy in Acute Coronary Syndromes: Adding Cilostazol to Aspirin and Clopidogrel?

Abstract: Dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor antagonist is the standard of care in acute coronary syndromes. Additionally, novel P2Y12 receptor antagonists such as prasugrel and ticagrelor are even recommended over clopidogrel in certain clinical guidelines. Despite the fact that clopidogrel is fraught with significant variability in on-treatment platelet reactivity, the novel P2Y12 receptor antagonists come at the price of increased side effects and cost.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…A total of 17 potentially eligible studies were reviewed and detailed evaluations were made. Among these, 5 trials were excluded because it was found that they did not meet the inclusion criteria after the full-texts were read (2 compared DAPT with triple antiplatelet therapy 18 , 19 ; 1 trial had an inconsistent outcome 20 ; and 2 trials were non-STEMI studies). 21 , 22 Finally, 12 RCTs 6 , 10 , 23 32 were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 potentially eligible studies were reviewed and detailed evaluations were made. Among these, 5 trials were excluded because it was found that they did not meet the inclusion criteria after the full-texts were read (2 compared DAPT with triple antiplatelet therapy 18 , 19 ; 1 trial had an inconsistent outcome 20 ; and 2 trials were non-STEMI studies). 21 , 22 Finally, 12 RCTs 6 , 10 , 23 32 were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the standard dual anti-platelet therapy of patients with CAD, aspirin and thienopyridine are recommended to be used in combination (14)(15)(16). Aspirin is an irreversible inhibitor of cyclooxygenase-1 that produces a permanent defect in thromboxane A2-mediated platelet activation (17), while thienopyridine prevents adenosine diphosphateinduced platelet activation and aggregation by irreversibly inhibiting the P2Y12 receptor (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in certain high-risk patients, one may opt for such an antiplatelet approach, once the benefits or equivalency are further established via direct comparative studies with the newer antiplatelet agents. 290 Until then, cilostazol has its niche in certain patient groups, including patients with PAD in decreasing symptoms and protecting patients after angioplasty and stenting, patients with CAD undergoing PCI in decreasing restenosis and enhancing DAPT, and in patients with stroke for secondary prevention and mitigating restenosis after carotid stenting, without increasing bleeding complications. Further comparative RCTs may provide additional robust evidence for expanding cilostazol's current indications and establishing these potential new indications, as detailed in this review.…”
Section: Conclusion/perspectivementioning
confidence: 99%